2019
DOI: 10.1080/1028415x.2019.1681066
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of peripheral tocopherol levels in age-related cognitive decline and Alzheimer’s disease

Abstract: Findings from observational studies and clinical trials on the associations between vitamin E and dementia remain controversial. Here we conducted a meta-analysis to determine the difference in blood tocopherols levels between patients with Alzheimer's disease (AD) or age-related poor cognitive function and healthy controls. Standardised mean difference (SMD) and 95% confidence intervals (CIs) were calculated and entered into a random effects model. Study quality, heterogeneity and publication bias were also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 69 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…The antioxidant activity of almonds has been best evaluated in two RCTs on habitual smokers, which showed some improvements of antioxidant biomarkers due to polyphenol compounds in the almond skins and suggested some antioxidant protection in smokers [124,125]. A metaanalysis of 31 articles indicated that individuals with AD, age-related cognitive impairment, or mild cognitive decline had lower circulatory concentrations of α-tocopherol compared to healthy controls [126]. Additionally, an analysis of 115 deceased and autopsied cases in the Rush Memory and Aging Project showed that higher levels of brain tocopherols such as α-tocopherol were related to lower activated microglia density in the cortical brain, which might protect against AD to lower levels of inflammation, amyloid, and neurofibrillary tangle severity [127].…”
Section: Almonds and Metabolic Health Biomarkers And Outcomesmentioning
confidence: 99%
“…The antioxidant activity of almonds has been best evaluated in two RCTs on habitual smokers, which showed some improvements of antioxidant biomarkers due to polyphenol compounds in the almond skins and suggested some antioxidant protection in smokers [124,125]. A metaanalysis of 31 articles indicated that individuals with AD, age-related cognitive impairment, or mild cognitive decline had lower circulatory concentrations of α-tocopherol compared to healthy controls [126]. Additionally, an analysis of 115 deceased and autopsied cases in the Rush Memory and Aging Project showed that higher levels of brain tocopherols such as α-tocopherol were related to lower activated microglia density in the cortical brain, which might protect against AD to lower levels of inflammation, amyloid, and neurofibrillary tangle severity [127].…”
Section: Almonds and Metabolic Health Biomarkers And Outcomesmentioning
confidence: 99%
“…Whatever the mechanism that links oxidative stress and tau pathology, there is some scope in exploring the utility of anti-oxidants, especially the easily available dietary forms, for the treatment of tauopathies. This is supported by a recent meta-analysis of several studies concludes that the circulating levels of a-tocophenol, the most bioavailable isoform of vitamin E, were significantly lower in AD patients and individuals with mild cognitive impairment, compared to age-matched controls (Ashley et al, 2019). However, the clinical trials investigating the therapeutic potential of antioxidants like vitamin C and E have yielded equivocal results (Dysken et al, 2014, La Fata et al, 2014, Farina et al, 2012, Beydoun et al, 2015and reviewed in Browne et al, 2019.…”
Section: The Prospects For Anti-oxidants Like Vitamin E As a Therapy For Tauopathiesmentioning
confidence: 95%
“…Some studies reported the association of the vitamin C, vitamin E, and their combined supplementation with better Mini Mental Scale Examination (MMSE) scores, verbal memory, and cognitive functioning in patients with dementia and AD [143][144][145]. In particular, vitamin E deficiency is being considered as a strong risk factor for development of AD and MCI and supplementation at higher doses has been recommended [146].…”
Section: Vitamins In Admentioning
confidence: 99%